Controversies and best practices for acute scaphoid fracture management. (January 2018) - Suh, Nina; Grewal, Ruby
Acute scaphoid fractures are common wrist injuries that continue to elicit debate from surgeons regarding the most appropriate diagnostic and management algorithms. This review will examine the current literature and trends, in an attempt to provide the reader with an evidence-based discussion regarding current controversies of interest to clinicians. In addition, an attempt will be made to provide recommendations for the best treatment practices for acute scaphoid fractures.